Penerapan Pajak Bunga Deposito Berjangka pada Pusat Koperasi Kredit Swadaya Utama - Sania, Sania; Dince, Maria Nona; Rengga, Andreas (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Credit cooperatives are also referred to as savings and loan cooperatives, savings and loan cooperatives are non-bank financial institutions in charge of providing services, in the form of deposits and other savings, income from stock and securities transactions in the form of loans and money storage for members. Based on Article 4 paragraph (2) of Law of the Republic of Indonesia Number 7 of 1983, and now Article 4 paragraph 2 of Law Number 36 of 2008. In its regulations, it is determined that on other income on the stock exchange, income from the transfer of property in the form of land and / or buildings and certain other income, the imposition of taxes is regulated by Government Regulations. The research method used is the Comparative Quantitative method. The results and conclusions of this study are that this study investigates the application of term deposit interest tax at the Main Self-Help Credit Cooperative Center. Inpractice, the Main Self-Help Credit Cooperative Center does not apply Final Income Tax Article 4 Paragraph 2 to Time Deposits at a rate of 10% but applies Article 23 Income Tax at a rate of 15%, this is due to the application of the interest tax rate on time deposits in the deposit depository cooperative is a legal entity not an individual. Keywords : Income Tax article 4 (2) on deposit interest, Savings and Loans Cooperative, Time Deposit,